Basal and Dynamic Leptin Secretion: Association with Cardiometabolic Risk and Body Weight Trajectories in African-Americans and European-Americans - Ebenibo, Sotonte; Edeoga, Chimaroke; Owei, Ibiye; Dagogo-Jack, Sam (Frontiers in Endocrinology, 2018)
Background Fasting plasma leptin levels reflect fat mass, but dynamic leptin responses to secretagogues, and the influence of race/ethnicity, have not been well studied. Here, we compared basal and stimulated leptin levels in relation to cardiometabolic risk and weight trajectories in black and white subjects. Subjects and methods We studied 254 (127 black and 127 white) normoglycemic adults enrolled in the Pathobiology of Prediabetes in a Biracial Cohort (POP-ABC) study. At baseline and annually, POP-ABC participants underwent physical examination, oral glucose tolerance test, and measurements of body fat (dual energy X-ray absorptiometry), fasting plasma leptin, insulin, cortisol, lipids, and leptin secretory response to single-dose (2 mg) dexamethasone (dex). The interactions among basal and stimulated leptin and changes in adiposity/cardiometabolic measures during the ensuing year were then analyzed. Results The mean (±SD) fasting leptin level (50.6 ± 47.7 vs. 39.5 ± 37.6 ng/mL, P = 0.004) and body mass index (BMI) (31.9 ± 7.14 vs. 29.0 ± 7.66 kg/m2, P = 0.0043) were higher in black women vs. white women, but similar in black men vs. white men (leptin: 12.4 ± 2.07 vs. 11.1 ± 1.40 ng/mL; BMI: 29.4 ± 7.68 vs. 28.1 ± 4.23 kg/m2). The peak leptin response to dex (~200% baseline) did not differ significantly by gender or race. Total body fat correlated positively with fasting leptin (r = 0.81, P < 0.0001) and inversely stimulated leptin levels (r = −0.26, P < 0.0001). Fasting leptin was unrelated to 1-year change in weight or fat mass, whereas stimulated leptin levels were significantly associated with 1-year trajectories in weight (P = 0.0016) and total fat mass (P = 0.0035). Stimulated leptin levels also had significant interactions with insulin sensitivity (homeostasis model of insulin resistance, P = 0.01), triglycerides (P = 0.0078), fasting glucose (P = 0.027), systolic blood pressure (P = 0.037), and high-sensitivity C-reactive protein (P = 0.027). Conclusion We found no significant ethnic disparities in basal or dynamic leptin secretion in relation to adiposity. Fasting leptin levels were not associated with 1-year weight change, while stimulated levels showed weak though significant association with 1-year weight change.